Kerja Sama Energi Hijau Amerika Serikat–Cina: Peluang dan Tantangan (2021–2024) - Aktalya, Fini; Alfajri, Alfajri; Siddiqy, Muhammad Arsy Ash (Journal of Political Issues, 2026)
Green energy cooperation between the United States and China emerged as a strategic effort to address global climate change during the period from 2021 to 2024. This research explores the dynamics of this cooperation, highlighting both the opportunities and challenges faced by the two countries. Employing a liberal interdependence theoretical framework, the study employs qualitative methods, with library research serving as the primary data collection technique. Despite existing geopolitical differences, both countries advanced green energy development under the leadership of Presidents Joe Biden and Xi Jinping. Opportunities for collaboration arose from various factors, including changes in leadership, enhanced dialogue, positive responses, global interdependence, formal agreements, and the strategic role of the Environmental Protection Agency (EPA). Key areas of cooperation encompassed investment in green technology, knowledge transfer, and collaborative research efforts. However, challenges during Biden's administration were inevitable and continued to persist even after the administration ended due to divergent domestic policies and priorities arising from changing leadership, technological competition, and ongoing political tensions. Greater difficulties are anticipated as Donald Trump returns to office. The study concludes that cooperation in green energy between these two major economic powers is vital for the global energy transition and efforts to mitigate climate change; nevertheless, significant challenges must be addressed to facilitate positive trends and achieve progress.